Sertifikasi Halal dan Tingkat Kesadaran Pelaku Usaha di Kota Pangkalpinang - Aswin Aswin; Yolanda Destiana (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This study aims to assess the extent of business actors' understanding of halal certification in Pangkalpinang City. The research employs a qualitative approach, with data collected from micro, small, and medium enterprises in Pangkalpinang, involving eight UMKM actors as informants. The findings reveal that most business actors have a fairly good awareness of the importance of halal certification for their products. However, the limited knowledge possessed by UMKM actors regarding certification leads to a lack of clear understanding of the procedures and application process. This situation is caused by the lack of outreach efforts from relevant parties, particularly the Pangkalpinang City government. Therefore, the government needs to make extra efforts to provide socialization and education to business actors so they can clearly understand the flow and procedures for halal certification registration for their products. In addition, the role of Halal Product Assistants (PPH) is also crucial, as they are directly involved with the community